KECENDERUNGAN PENELITIAN COLLABORATIVE GOVERNANCE DI INDONESIA : DARI DESAIN PENELITIAN HINGGA ANALISIS DATA : Government bureaucracy - Indra Aditya; Fajar Akbar (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
Important collaborative efforts are made by several institutions or organizations in solving problems and to achieve goals. In the implementation of collaborative governance there are still many obstacles and obstacles that hinder collaboration. The aim is to find out trends in collaborative governance research starting from research design, data sources, research instruments, data analysis, number of publications, types of research, research subjects, treatments, data collection instruments and data analysis methods. This study uses content analysis of a number of articles obtained through publish or perish applications from journals in Indonesia from 2012 to 2022, with collaborative governance as the main focus of the study. The current study reveals that the number of publications since 2019, 2020 and 2021 has increased higher than in previous years. However, there has been a decline in the last two years. Among these publications, all research designs used were qualitative. In addition, local government and programs are the most researched subjects, respectively. Interviews and descriptive analysis are the most commonly used data analysis instruments and methods.